Turbulent flow over a wavy boundary - Cermak, Jack E., author; Beebe, P. S., author; Fluid Dynamics and Diffusion Laboratory, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1972)
An experimental study was made of turbulent flow over a wavy surface. Sinusoidal waves of three sizes were used to explore the variations of flow with wave size. Measurements of mean and turbulent velocities were taken with a two-wire method. Local heat transfer rates and pressures on the wavy surface were also measured. An equilibrium turbulent boundary layer, which conforms to Rotta's and Clauser's self-preservation requirements, develops in the region far downstream from the first wave. In the lower portion of this layer, the mean velocity is represented by the logarithmic velocity profile when the form-drag measurements of skin friction are used to determine the shift-in-origin. The roughness function is related to the wave height since the wavy surface is shown to be a "k" type surface. The velocity defect profile in the logarithmic form extends to higher values of yu*/ϐ*U∞ than those for smooth wall flows. Eddy viscosity results support the assumed logarithmic velocity variation in the lower part of the boundary layer. Measurements of shear stress by either the two-wire or the heated-film method disagree with the form drag measurements of skin friction. The wavy surface is an extended surface windbreak since it reduces the overall wind speed above the surface and creates vortices between the waves. However, surface shear stresses are increased, and the erosion rate of field waves is a function of wave height.
CER71-72PSB-JEC44.
May 1972.
Keywords: Hydrodynamics; Turbulence